Elevation Potential among Circuit Court Nominees and Its Effect on the Senate's Confirmation Behavior. (March 2020) - Badas, Alex
Using traits conventionally believed to lead to elevation from the Circuit Courts to the Supreme Court, this paper uses an item response theory model to estimate latent elevation estimates for each Circuit Court judge nominated and confirmed between 1901 and 2017. I validate this measure by showing that it predicts which Circuit Court judges are promoted to the Supreme Court and which end up on the president's Supreme Court shortlist. Furthermore, I investigate how the Senate strategically responds to the nomination of Circuit Court nominees with high elevation estimates. The Senate takes longer to confirm nominees with high elevation scores and is less likely to confirm them by voice vote, and these nominees receive a greater share of nay votes. This paper concludes by suggesting additional uses for the elevation estimates.